2011
DOI: 10.1002/mrm.22891
|View full text |Cite
|
Sign up to set email alerts
|

Saturation power dependence of amide proton transfer image contrasts in human brain tumors and strokes at 3 T

Abstract: Amide proton transfer (APT) imaging is capable of detecting mobile cellular proteins and peptides in tumor and monitoring pH effects in stroke, through the saturation transfer between irradiated amide protons and water protons. In this work, four healthy subjects, eight brain tumor patients (four with high-grade glioma, one with lung cancer metastasis, and three with meningioma), and four stroke patients (average 4.3 6 2.5 days after the onset of the stroke) were scanned at 3 T, using different radiofrequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
156
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(172 citation statements)
references
References 41 publications
15
156
1
Order By: Relevance
“…APT-weighted CEST MR imaging resulted in a strong correlation of APT effect with pH levels because proton exchange reduced strongly during the pH level reduction, owing to ischemia (25)(26)(27)(28)(33)(34)(35)44,45). Therefore, the diminished CEST effect in the ischemic area was mainly due to a change in pH level.…”
Section: Thoracic Imaging: Chemical Exchange Saturation Transfer Mr Imentioning
confidence: 99%
See 1 more Smart Citation
“…APT-weighted CEST MR imaging resulted in a strong correlation of APT effect with pH levels because proton exchange reduced strongly during the pH level reduction, owing to ischemia (25)(26)(27)(28)(33)(34)(35)44,45). Therefore, the diminished CEST effect in the ischemic area was mainly due to a change in pH level.…”
Section: Thoracic Imaging: Chemical Exchange Saturation Transfer Mr Imentioning
confidence: 99%
“…In tumors, on the other hand, the intracellular exchangeable proton content became higher than that in normal tissue, while the intracellular pH level remained approximately unchanged, so that the CEST effect increased (23,27). Additionally, the effect of CEST resulted in a significant difference between glioma and normal tissue, as well as the development of edema or an ischemic area, including radiation necrosis (23,27,31,(44)(45)(46)(47). Moreover, the effect of CEST produced a significant difference between malignant and benign with high MTR asym (at 3.5 ppm).…”
Section: Thoracic Imaging: Chemical Exchange Saturation Transfer Mr Imentioning
confidence: 99%
“…An off-resonance continuous-wave radiofrequency saturation pulse was used. APT single-section imaging was performed, and the saturation time, at 2 T excitation power, was 500 ms (the maximum time available for this body coil [22][23][24] ). The acquisition mode was TSE, and the factor was 38.…”
Section: Apt Data Acquisition and Processingmentioning
confidence: 99%
“…Saturation times of 3 and 4 s gave better contrast between ischemic regions and the NAB, as compared to 5 s. This may come from a coexisting solid macromolecular MT effect (9,13) that is more pronounced at a higher RF power, or possible intra-and inter-molecular nuclear Overhauser effects (10). Similar results were obtained by Sun et al (9), who showed that the optimal saturation power is achieved at around 1 μT, and APT contrast decreased at higher power fields.…”
Section: Discussionmentioning
confidence: 94%
“…The study showed that the optimal RF power is approximately 1 μT on 3T, which sufficiently labels the exchangeable protons with minimal spillover effects. On the other hand, Zhao et al (10) showed that a 2 μT amplitude had better APT difference compared to 1 or 3 μT, but the study was based on a duration of 500 ms. We adopted an amplitude of 1.2 μT, in order to maximize the pH-weighted effect using 3T TSE imaging.…”
Section: Apt Imaging Acquisition Theoretical Background For Apt Expermentioning
confidence: 98%